The Pentecostal Hypothesis: Christ Talks, They Decide: Oleh Nimi Wariboko - Monte Lee Rice (Asosiasi Teolog Indonesia, 2021)
This is a book review of The Pentecostal Hypothesis: Christ Talks, They Decide.